2019
DOI: 10.3176/oil.2019.1.05
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Composition and Pyrolysis Characteristics of Thermal Bitumen Derived From Pyrolyzing Huadian Oil Shale, China

Abstract: Thermal bitumen is an important intermediate derived from kerogen decomposition during oil shale pyrolysis. In this study, thermal bitumen was obtained by extracting oil shale char generated from pyrolysis of Huadian oil shale at 360-530 °C. The chemical composition and pyrolysis characteristics of bitumen were investigated by ultimate analysis, liquid chromatography fractionation, Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). The decomposition of oxygencontaining structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The length of aromatic side chains and the degree of condensation of aromatic rings of the AR and RE are much higher than SA. Additionally, the 13 C-NMR analysis indicated that SA mainly consists of chain alkanes with a few cycloalkanes, whereas AR and RE contain more content of thick-ring aromatic hydrocarbons. R A and R N increase significantly, which indicated that the association degree of RE is significantly higher than those of SA and RE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The length of aromatic side chains and the degree of condensation of aromatic rings of the AR and RE are much higher than SA. Additionally, the 13 C-NMR analysis indicated that SA mainly consists of chain alkanes with a few cycloalkanes, whereas AR and RE contain more content of thick-ring aromatic hydrocarbons. R A and R N increase significantly, which indicated that the association degree of RE is significantly higher than those of SA and RE.…”
Section: Discussionmentioning
confidence: 99%
“…The relative molecular weight was determined by an Agilent-11006 (Agilent, USA) under the conditions of a sample mass of 2 mg, tetrahydrofuran being a solvent, a flow rate of 0.6 mL/min, and a column temperature of 40 °C. Using a Varian Inova-400 superconducting NMR instrument (Varian, USA), deuterated chloroform as a solvent, and tetramethylsilane an internal standard, 1 H-NMR and 13 C-NMR of samples were analyzed at ambient temperature. ■ REFERENCES…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations